Pelatihan dan Pengembangan yang Berguna untuk Meningkatkan Kinerja Karyawan di Industri Jasa - Muhammad Fahmy Mayadi; Zikri Bagas Munandar; Syeihan Aulia Rizkiadi (Trending: Jurnal Manajemen dan Ekonomi, 2026)
The service sector in Indonesia plays a big role in the country’s economy, making up more than 56% of the national GDP. However, it struggles with high employee turnover, often reaching 25 to 30%. This problem is mainly because employees don’t see enough chances to grow and improve themselves, not just because of money issues. This study looks at how training and development, which are non-money benefits, can help improve employee performance. The research uses a literature review, gathering information from academic papers, books, and recent reports from sources like LinkedIn Learning and Gallup. The findings show that training helps workers get better at their jobs and work more efficiently. Career development, on the other hand, helps keep employees motivated and loyal in the long run. Both training and career growth are important for increasing productivity and making services better. The study also found that employees who receive training perform 21% better than those who don’t. In short, service businesses should see training and development as important investments in their people, not just as expenses. This helps keep employees and supports the long-term success of the business.